2018
DOI: 10.1016/j.apcata.2018.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol dehydration to hydroxyacetone in gas phase over copper supported on magnesium oxide (hydroxide) fluoride catalysts

Abstract: et al.. Glycerol dehydration to hydroxyacetone in gas phase over copper supported on magnesium oxide (hydroxide) fluoride catalysts. Applied Catalysis A : General, Elsevier, 2018, 557, pp. Abstract:The dehydration of glycerol to hydroxyacetone was studied over copper-based catalysts using magnesium oxide (hydroxide) fluoride with various F/Mg ratio as support of copper. After calcination at 350°C, the incorporation of copper, mainly at + II oxidation state, into the support lattice was observed for MgO and MgF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 67 publications
3
29
0
Order By: Relevance
“…It was already reported that this type of catalyst exhibited virtually only acidity. 40,47 This is here confirmed by the characterization of acid-base properties using both CO and CO 2 probe molecules. As proposed by Kikhtyanin et al, 26 such reaction was rather catalyzed by Brønsted acid sites explaining, at least in part, the poor catalytic properties of MgF 2 for aldol condensation of furfural.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…It was already reported that this type of catalyst exhibited virtually only acidity. 40,47 This is here confirmed by the characterization of acid-base properties using both CO and CO 2 probe molecules. As proposed by Kikhtyanin et al, 26 such reaction was rather catalyzed by Brønsted acid sites explaining, at least in part, the poor catalytic properties of MgF 2 for aldol condensation of furfural.…”
supporting
confidence: 73%
“…Such solids were successfully used as either basic catalysts for the Michael addition of 2-methylcyclohexane-1,3-dione to methyl vinyl ketone (25 °C, atmospheric pressure) 35 or catalytic support. [36][37][38][39][40] Moreover, the use of solid basic catalysts involves generally an activation step at high temperature to active basic sites by removal of carbonate species.…”
Section: 32mentioning
confidence: 99%
“…Basic promoters, such as liquid alkalis and solid bases, are knownt op romote dehydrogenationr eactions of polyols and alcohols. [52] Zhou and co-workers reportedaseries of Cu/oxide (SiO 2 ,M gO, Al 2 O 3 ,a nd ZnO) catalysts for glycerol conversion. [50] Their experimental resultss howed that, although both glycerol conversion and 1,2-PDO selectivity were very poor without an external H 2 source (X < 25 %, S % 12 %), the addition of MeOH or 2-PrOH as ac osolvent led to 67 %s electivity to 1,2-PDO.…”
Section: Cth-ii Routementioning
confidence: 99%
“…In a previous work, we have shown that the amount of CO2 adsorbed in the monolayer is directly linked to the basic site number present at the material surface [32]. CO2 monolayer content was calculated from the analysis of CO2 adsorption isotherm by BET model.…”
Section: Al2o3 Synthesis and Characterizationmentioning
confidence: 99%